Delving into the Critical Thinking Skills of Pre-Service Mathematics Teachers with Their Metacognitive Awareness - Erdoğan, Fatma; Kalkan, Sinan (Ozgen Korkmaz, 2024)
Metacognitive awareness (MA) and critical thinking (CT) are crucial higher-order thinking skills in mathematics education. MA and CT skills of pre-service teachers are considered important predictors of their future teaching practices in the teaching and learning of mathematics. In this context, the study examines the potential effects of socio-demographic (e.g., gender) and academic variables (e.g., academic year and academic achievement) on MA and CT skills of pre-service mathematics teachers (PSTs). Additionally, the aim of this study is to explore the relationship between the MA and CT skills of PSTs. Employing a quantitative research methodology, the study was structured around a correlational model. It involved 218 PSTs, using the “MA Inventory” and “CT Standards Scale” for data collection. The data were analyzed through independent sample t-test, one-way analysis of variance, correlation analysis, and simple linear regression analysis. The findings indicate that PSTs possess a high level of MA and CT skills. Significant differences in MAs of PSTs were observed with respect to academic year and academic achievement, while the CT skills of PSTs showed significant differences concerning gender and academic achievement. A strong, positive, and significant correlation was found between MA and CT skills of PSTs. Furthermore, the MAs of PSTs were identified as a significant predictor of their CT skills, explaining 38% of the variance in CT skills. © 2024, Ozgen Korkmaz. All rights reserved.
Keywords: critical thinking; higher education; mathematics education; metacognition; pre-service teacher